Protuberant Electrode Structures for Subretinal Electrical Stimulation: Modeling, Fabrication and in vivo Evaluation - Losada, Pedro González; Rousseau, Lionel; Grzeskowiak, Marjorie; Valet, Manon; Nguyen, Diep; Dégardin, Julie; Dubus, Elisabeth; Picaud, Serge; Lissorgues, Gaelle (Frontiers in Neuroscience, 2019)
Many neural interfaces used for therapeutic applications are based on extracellular electrical stimulation to control cell polarization and thus functional activity. Amongst them, retinal implants have been designed to restore visual perception in blind patients affected by photoreceptor degeneration diseases, such as age-related macular degeneration (AMD) or retinitis pigmentosa (RP). While designing such a neural interface, several aspects must be taken into account, like the stimulation efficiency related to the current distribution within the tissue, the bio-interface optimization to improve resolution and tissue integration, and the material biocompatibility associated to long-term ageing. In this study, we investigate the use of original microelectrode geometries for subretinal stimulation. The proposed structures combine the use of 3D wells with protuberant mushroom shaped electrode structures in their bottom implemented on a flexible substrate that allows the in vivo implantation of the devices. These 3D microelectrode structures were first modelled using finite element analysis. Then a specific microfabrication process compatible with flexible implants was developed to create the 3D microelectrode structures. These structures were tested in-vivo in order to check the adaptation of the retinal tissue to them. Finally, preliminary in-vivo stimulation experiments were performed.